Penerapan Algoritma Diffie Hellman Key Exchange dalam Komunikasi Data Antarnode pada Wireless Sensor Network - Holden Gunawan; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
One key exchange method that has been developed is Diffie-Hellman key exchange (DHKE), which can be used to securely create shared secrets between the two devices over an unsecured network. The two devices running this algorithm have their own secret variables, exchange two public variable values, and perform calculations using accepted variables as well as randomly obtained secret variables to obtain shared secretes. In this study built a system with ESP32 microcontroller as data processing, has Cryptographic hardware acceleration one of which is a random number generator (RNG), supporting Wi-Fi communication protocols. The DHT11 sensor collects data with measuring parameters and is transmitted to a gateway connected to ESP32 and monitored wirelessly. Average computing time and delivery from ESP-1 to ESP-2 and ESP-3 is 0.084 seconds and 0.079 seconds.While the delivery from ESP-2 and ESP-3 to ESP-1 amounted to 3.315 seconds and 3.307 seconds. It can be concluded that the factors that affect the length of delivery time are client requests first to the server and queues on the server in serving the client.